2018
DOI: 10.1097/mcg.0000000000000791
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Self-directed Versus In-Classroom Education of Narrow Band Imaging in Diagnosing Colorectal Polyps Using the NICE Criteria

Abstract: Using a standardized educational tool, the accuracy of distinguishing adenomatous versus hyperplastic colon polyps using NBI between the in-class teaching and self-directed learning were similar. This suggests that both training methods can be utilized for the education of medical trainees in the use of NICE criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…no difference in optical diagnosis performance was found between trainees randomized to online self-learning or didactic classroom teaching [86,87]. In the study of Smith et al [87], 16 trainees were randomized to receive online self-learning (n = 8) or didactic training (n = 8) using identical teaching materials and videos.…”
Section: Recommendationmentioning
confidence: 99%
“…no difference in optical diagnosis performance was found between trainees randomized to online self-learning or didactic classroom teaching [86,87]. In the study of Smith et al [87], 16 trainees were randomized to receive online self-learning (n = 8) or didactic training (n = 8) using identical teaching materials and videos.…”
Section: Recommendationmentioning
confidence: 99%
“…No difference in diagnostic accuracy for the prediction of diminutive/small polyp histology was found between trainees who received didactic training and those who followed the computer-based program. Allen et al [86] also found no difference in the accuracy of distinguishing adenomatous versus hyperplastic colon polyps between in-class teaching and online learning.…”
Section: B Training/learning Steps For Optical Diagnosismentioning
confidence: 96%
“…have all shown efficacy for the initial steps of optical diagnosis learning [5 -7, 9, 49, 52, 67, 80 -84]. In two head-to-head comparisons, ▶ no difference in optical diagnosis performance was found between trainees randomized to online self-learning or didactic classroom teaching [86,87]. In the study of Smith et al [87], 16 trainees were randomized to receive online self-learning (n = 8) or didactic training (n = 8) using identical teaching materials and videos.…”
Section: B Training/learning Steps For Optical Diagnosismentioning
confidence: 99%
“…Two studies examined the learning curves of self-directed learning and in-classroom education about VC and compared the accuracy and confidence level of polyp characterization between them. 33,34 Both studies demonstrated that there was no benefit for the in-classroom session over selfdirected learning. Daly et al found similar results in another study, comparing in-classroom and self-learning in assessing dysplastic changes in BE.…”
Section: Implications For Patient Carementioning
confidence: 99%